Fertilizers in Vietnam - Thang, Tran Toan (International Food Policy Research Institute, 2014)
Although agriculture only contributes 20 percent to GDP in Vietnam, over 70 percent of the population relies on the sector. Rice is the most important crop in Vietnam accounting for 90 percent of total grain output. The agricultural sector has faced recent challenges due to urbanization and industrialization, as well as few opportunities for increasing cultivated land area. Increased crop yields through the use of chemical fertilizer is one of the few methods available for increasing agricultural output.